The impact of abusive supervision on employee counterproductive work behavior: a moderated mediation analysis - Li, Jingli; Xu, Guangnuo (Frontiers in Psychology, 2025)
IntroductionThis study explores how abusive supervision impacts employee counterproductive work behavior (CWB), highlighting the mediating roles of emotional exhaustion and ingratiation behavior, and the moderating role of core self-evaluation.MethodsDrawing on self-regulation theory and resource conservation theory, the paper tests a moderated mediation model using a three-wave survey of 198 employees.Result and discussionResults indicate that abusive supervision directly increases CWB, with emotional exhaustion serving as a positive mediator and ingratiation behavior serving as a negative mediator. Core self-evaluation moderates both mediation paths. These findings provide new insights into the dual psychological mechanisms underlying workplace deviance and suggest practical strategies for mitigating abusive leadership.